Validity and Practicality of Kvisoft Flipbook Maker Media Using Problem Based Learning in Learning Pancasila Education in Elementary School - Ulfa, Elfa Sri Surya; Reinita, Reinita; Ladiva, Hasmai Bungsu; Ahmad, Syafri (research, training and philanthropy institution Natural Aceh, 2025)
The background of this research is the use of image media or displays in learning Pancasila Education, which makes students less focused and difficult to understand the lessons. This research aims to develop a valid and practical Kvisoft Flipbook Maker interactive media. This research uses the Research and Development (R&D) method with the ADDIE model. The data was obtained through validation questionnaire and the practicality teachers and grade IV students at SDN 22 and 24 Ujung Gurun, as well SDN 26 Rimbo Kaluang. The results of study showed that the Kvisoft Flipbook Maker learning media was very valid with a score of 93.33% by material experts, 90% by linguists and 92% by media experts, with an average validity of 91.77%. The results of the practicality test showed that the learning media was very practical with a score of 96% by teachers and 94% by students of SDN 22 Ujung Gurun, as well as 94% by teachers and 95% by students of SDN 24 Ujung Gurun, and 98% by teachers and 98% by students of SDN 26 Rimbo Kaluang. Therefore, the interactive media Kvisoft Flipbook Maker valid and practical to use in learning Pancasila Education in grade IV of Elementary School.